2020
DOI: 10.15311/selcukdentj.545065
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and behavior regarding oral hygiene among in a group university students: A Self-reported

Abstract: Background: The aim of this study is to evaluate the factors of oral hygiene habits, tooth brushing motivation and toothpaste preference factors.Materials and methods: This cross-sectional study based on the hospital was carried out by surveying 759 university students over 18 years of age. The demographics, duration and frequency of self-reported questionnaire oral hygiene habits, motivation source in tooth brushing and effective factors in the selection of toothpaste were investigated.The level of statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In contrast to our study, it also reported that urban residency was a favourable factor for dentist visits (aOR = 1.9, p < 0.05) and suggested a higher number of oral health professionals in this country (1400 dentists, one per 20,000 inhabitants), with the highest density of workers in an urban area [28]. Moreover, the specific source of motivations for cleaning teeth or toothpaste selection among young adults was the fear of losing teeth and the whitening feature of teeth [29].…”
Section: Urban Residency and Young Adultsmentioning
confidence: 99%
“…In contrast to our study, it also reported that urban residency was a favourable factor for dentist visits (aOR = 1.9, p < 0.05) and suggested a higher number of oral health professionals in this country (1400 dentists, one per 20,000 inhabitants), with the highest density of workers in an urban area [28]. Moreover, the specific source of motivations for cleaning teeth or toothpaste selection among young adults was the fear of losing teeth and the whitening feature of teeth [29].…”
Section: Urban Residency and Young Adultsmentioning
confidence: 99%
“…In contrast to our study, it also reported the urban residency as the favorable factor to the dentist visit (aOR=1.9, p<0.05), and suggest higher number of oral health professional in this country (1400 dentists, one per 20000 inhabitants), with a highest density of workers in an urban area [26]. Moreover, the speci c source of motivations for cleaning teeth or toothpaste selection among young adults were the fear of losing of teeth and the whitening feature of teeth [27].…”
Section: Sociodemographic Factor Correlates With Oral Hygiene Practicesmentioning
confidence: 98%